Assessment of criteria affecting decision making for retrofitting an existing building with a green roof. - Abidin, Nur Izieadiana (2023)
Buildings are one of the significant sources of energy consumption triggering the threat of greenhouse and climate changes. In a building, a green roof offers significant perks of energy reductions through heat loss. Past studies have focused on modern methods of roof designing to overcome sustainability issues; however, the path of existing buildings is still unpaved. This paper aims to analyse influential criteria for the decision-making for retrofitting an existing building with green roof initiatives. For this purpose, a survey instrument with 36 measurement items was designed and distributed to Architects. Factor analysis and reliability analysis were used to analyse the data in SPSS software. Criteria affecting retrofitting an existing building with a green roof were discussed and classified into economic, site, and design criteria. The analysis results indicated that the highest priority is given to Site criteria for retrofitting with a green roof. The Site criteria attained the highest Factor Score (FS) values of 0.687, followed by Design criteria with FS of 0.623, and Economic criteria with the least FS value of 0.570. The development of criteria in this study is valuable for the decision-makers while retrofitting an existing building to improve the current energy performance and design more conducive structures. The criteria developed allow dealing with an informative approach and influence the target effective in achieving sustainability in an existing building to ease the process of retrofitting assessment by looking into the consequences, uncertainties, and possible outcomes.